2014
DOI: 10.20452/pamw.2499
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease and kidney transplantation‑evaluation of potential transplant recipient

Abstract: Nowadays, from 50% to 60% of deaths can be directly attributed to CVD, with an incidence of ischemic heart disease being approximately 1 per 100 person-years at risk. 3 In contrast, some older studies reported that between 17% and 50% of deaths in kidney transplant recipients were due to CVD. 4 Moreover, CVD is the most common cause of death in kidney allograft recipients with a functioning graft, and accounts for 30% of overall graft loss from death, with the greatest rates in Cardiovascular disease and kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The prevalence of atrial fibrillation (AF) in patients with chronic renal failure undergoing hemodialysis is 2–3 times higher than the general population [ 1 , 2 , 3 , 4 , 5 ]. Hemodialysis patients are closely associated with the risk factors for the development of AF such as aging, hypertension, diabetes mellitus, coronary artery disease, and heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of atrial fibrillation (AF) in patients with chronic renal failure undergoing hemodialysis is 2–3 times higher than the general population [ 1 , 2 , 3 , 4 , 5 ]. Hemodialysis patients are closely associated with the risk factors for the development of AF such as aging, hypertension, diabetes mellitus, coronary artery disease, and heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Although NOACs are nowadays the preferred therapeutic option according to European Society of Cardiology guidelines, patients with markedly reduced renal function, especially with eGFR < 30 ml/min, benefit from VKA treatment [35] . Also patients after kidney transplantation are limited to use of VKA [36,37,38] . From AF -atrial fibrillation Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some patients, in particular with diabetes, may require either percutaneous coronary intervention (PCI) or cardiac artery bypass grafting (CABG). Thus as reviewed previously, cardiovascular evaluation of potential kidney allograft recipients is of utmost importance [ 16 ]. A meta-analysis suggested that the strategy of CABG is better than PCI with DES for diabetic patients with multivessel CAD [ 17 ].…”
mentioning
confidence: 99%